2009
DOI: 10.1016/j.molcel.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Src-Induced Disassembly of Adherens Junctions Requires Localized Phosphorylation and Degradation of the Rac Activator Tiam1

Abstract: The Rac activator Tiam1 is required for adherens junction (AJ) maintenance, and its depletion results in AJ disassembly. Conversely, the oncoprotein Src potently induces AJ disassembly and epithelial-mesenchymal transition (EMT). Here, we show that Tiam1 is phosphorylated on Y384 by Src. This occurs predominantly at AJs, is required for Src-induced AJ disassembly and cell migration, and creates a docking site on Tiam1 for Grb2. We find that Tiam1 is associated with ERK. Following recruitment of the Grb2-Sos1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 38 publications
2
75
1
Order By: Relevance
“…Cell lysates were obtained by centrifugation at 14,000 ϫ g for 15 min, and protein concentration was determined by Bradford protein assay (Beyotime). 20 l of cell lysates (about 30 g of protein) were firstly mixed with 70 l of reaction buffer and then incubated with 10 l of acetylAsp-Glu-Val-Asp p-nitroanilide (2 mM) in a 96-well plate for 2 h at 37°C. Caspase 3 activity was measured through the substrate p-nitroanilide at an absorbance at 405 nm in a microplate spectrophotometer (Thermo).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lysates were obtained by centrifugation at 14,000 ϫ g for 15 min, and protein concentration was determined by Bradford protein assay (Beyotime). 20 l of cell lysates (about 30 g of protein) were firstly mixed with 70 l of reaction buffer and then incubated with 10 l of acetylAsp-Glu-Val-Asp p-nitroanilide (2 mM) in a 96-well plate for 2 h at 37°C. Caspase 3 activity was measured through the substrate p-nitroanilide at an absorbance at 405 nm in a microplate spectrophotometer (Thermo).…”
Section: Methodsmentioning
confidence: 99%
“…T cell lymphoma invasion and metastasis 1 (Tiam1) serves as a specific GEF for Rho GTPase Rac1 (16). Although it has been well established that Tiam1 plays important roles in tumor progression and metastasis (17)(18)(19)(20), the specific mechanisms regulating its activity and protein stability are far from clear (21,22). It has been reported that Src-induced adherens junction disassembly and cell migration involve phosphorylation and degradation of Tiam1, likely through calpain proteases (20).…”
mentioning
confidence: 99%
“…Several signaling pathways and proteases have been reported to be involved in the degradation of Tiam1 protein, in particular activation of calcium-dependent calpain proteases (Qi et al, 2001;Woodcock et al, 2009). Induction of senescence in various cell types triggers a DNA damage response that then triggers activation of calpain proteases (Demarchi et al, 2010).…”
Section: Rmfs Undergo Stress-induced Senescencementioning
confidence: 99%
“…Treatment of cultured cells with the calpain inhibitor ALLN during induced senescence led to toxic cell death at all doses tested. Therefore, we performed an in vitro Tiam1 cleavage assay based on similar in vitro protease assays reported previously (Li et al, 1997;Juo et al, 1998;Qi et al, 2001;Woodcock et al, 2009). Tiam1 immunoprecipitates from cells with exogenous Tiam1 expression Pre, pre-senescent cells; H2O2, hydrogen peroxide; Bleo, bleomycin; C, control pBabe RMF; Lys, loading control lysate for position of the full-length Tiam1 band, also indicated by an arrow.…”
Section: Rmfs Undergo Stress-induced Senescencementioning
confidence: 99%
“…Tyrosine phosphorylation of E-cadherin by Src targets it for ubiquitination-dependent endocytosis and degradation, thus limiting its availability at cell-cell contacts (Behrens et al, 1993;Fujita et al, 2002;Palacios et al, 2005). Tyrosine phosphorylation of other AJ-localized Src substrates such as the Rho-GEF, Tiam1, also contributes to the disruption of AJs in human malignancies (Woodcock et al, 2009).…”
Section: Introductionmentioning
confidence: 99%